1978
DOI: 10.1007/bf01851410
|View full text |Cite
|
Sign up to set email alerts
|

Haemodialysis in rats

Abstract: A plate dialyser requiring an extracorporeal blood volume of 1.5 ml was developed to dialyse conscious rats. In experiments in vitro and in vivo its function was tested. The in vitro clearances of urea, creatinine and potassium were 126+/-9 ml/min/m2, 70.5+/-9 ml/min/m2, and 132.5+/-13 ml/min/m2, respectively. The method appears to be suitable for pharmacological and toxicological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Therefore, this is the first study to evaluate drug dialyzability using in vivo model and extrapolate the drug dialyzability from in vivo model to human. On the benefits of this model, HD rat more reflects clinical condition than previous studies [4,5,[33][34][35], such as…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this is the first study to evaluate drug dialyzability using in vivo model and extrapolate the drug dialyzability from in vivo model to human. On the benefits of this model, HD rat more reflects clinical condition than previous studies [4,5,[33][34][35], such as…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, HD rat which can reflect Vd and evaluate drug removal rate is higher predictability of drug removal than in vitro drug clearance of dialyzer. Moreover, several previous studies have shown that in vivo HD models were used for evaluating the dialyzer performance or the change of physiological parameters in HD [4,5,[33][34][35][36], but the drug dialyzability using in vivo model has never been reported. Therefore, this is the first study to evaluate drug dialyzability using in vivo model and extrapolate the drug dialyzability from in vivo model to human.…”
Section: Discussionmentioning
confidence: 99%
“…The dialysis procedures were modified according to the methods described earlier [29][30][31]. The hollow-fiber dialysis membranes Cupro, Hemo, and AN69 were placed into minidialyzers (courtesy of Dr. J. Vienken, AKZO.…”
Section: Hemodialysis Sessionsmentioning
confidence: 99%